(untitled) (Revista de História Regional, 2008)
This article is constructed by the transcript of two documents relating to the installation of the Military Colony in Fóz do Iguaçu, in the triple border region of Brazil - Paraguay - Argentina. The installation of this military venture represents, in all the political and governmental strategies of the Empire, one of the milestones of the integration of regional borders in Brazil. The documentation consists of two annual reports, which were prepared, respectively, in the years 1897 and 1898, by Joaquim de Salles human Torres, administrator of the Colony, designated in1897, by the Office of the then State Minister of War, in the capital of the Empire. This documentary corpus is significant to the extent that the information contained therein enables the immertion in a universe of personal impressions and new knowledge about this region of international borders. As the historiographic production in Paraná crystallized knowledge about this military venture, for the privilege of certain sources, our intention is to socialize the contents of the two annual reports, enabling new readings on the Military Colony of Foz do Iguacu.